Pengaruh Media Sosial Instagram dan Atraksi Wisata terhadap Keputusan Berkunjung Wisatawan ke Wisata Puncak Pinus Becici, Yogyakarta - Eksitasari, Ayu Dianapramesti; Rahmatin, Leily Suci (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
Social media is one of the promotional tools that influence tourists' visiting decisions. Through social media, especially Instagram, tourists can easily access the official accounts of the tourist attractions they are going to. Tourist decisions can be influenced by several factors, namely tourist attractions, ease of accessibility and also reviews from other visitors. This research focuses on the influence of Instagram social media and tourist attractions on tourist interest in visiting. This study will try to find out how the influence of the two independent variables on the dependent variable. The research method in this study is quantitative research with sampling using probability sampling techniques. This research was conducted at Becici Pine Peak, Yogyakarta, by distributing questionnaires to visitors who came. From the results of distributing questionnaires, it was found that the majority of visitors came from within the Yogyakarta area and had an average age of 20 to 30 years. The results showed a significant influence between the 2 independent variables (X1) and (X2) with the dependent variable (Y). The presence of social media such as Instagram makes it easier for tourists to make decisions before visiting Becici Pine Peak, Yogyakarta.